Comparative Performance of Digital Signature Security Using Cryptography AES 192 BIT and RSA 512 BIT Algorithm Model (Journal of Advances in Information Systems and Technology, 2020)
Digital signatures are proof of authenticity and have the same function as a signature on a printed document, but the implementation is on digital documents. Public key cryptography or asymmetric keys are widely used in the implementation of data security on information and communication systems. The Rivest-Shamir-Adleman (RSA) algorithm is one of the most popular and widely used public key cryptography because of its less complexity. RSA has two main functions namely the process of encryption and decryption process. This research was made to find out an explanation and discussion of the optimal algorithm for the performance of digital signature data security by comparing the performance of the RSA 512 bit and AES 192 bit algorithms with this, which is expected to provide knowledge about the security performance of digital signatures which in the future can be further developed in order to obtain security.